Generation Z Motivation in Choosing a Career in the Digital Age - Heskyel Pranata Tarigan (Social Sciences Journal, 2026)
The development of digital technology has brought significant changes to the mindset and career preferences of Generation Z. This generation is known as a group that grew up with the advancement of the internet, social media, and digital transformation, thus having different views in determining career choices compared to previous generations. This study aims to analyze the motivations of Generation Z in choosing a career in the digital era and the factors that influence these decisions. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and literature studies. The results show that the main motivations of Generation Z in choosing a career include work flexibility, opportunities for self-development, work-life balance, competitive income, and the opportunity to work according to interests and passions. In addition, the influence of social media, technological developments, and digital work trends are also important factors in shaping their career orientation. Generation Z tends to choose jobs that provide freedom, creativity, and opportunities for professional and personal development. Thus, companies and educational institutions need to understand the characteristics and needs of Generation Z in order to be able to create a work environment and education system that is relevant to the demands of the digital era.